2017
DOI: 10.1093/cid/cix651
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Antibiotic Stewardship Programs in US Acute Care Hospitals: Findings From the 2015 National Healthcare Safety Network Annual Hospital Survey

Abstract: To assess uptake of the Centers for Disease Control and Prevention's Core Elements of Hospital Antibiotic Stewardship Programs, we analyzed stewardship practices as reported in the 2015 National Healthcare Safety Network's Annual Hospital Survey. Hospital uptake of all 7 core elements increased from 40.9% in 2014 to 48.1% in 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 4 publications
0
31
1
Order By: Relevance
“…Stewardship programs are extensively used in the United States and compliance with the various recommendations is monitored annually by the National Healthcare Safety Network Annual Hospital Survey (3,4). In Spain, different scientific societies promoted the development of a consensus document for optimizing the use of antimicrobials in hospitals (PROA project) (5).…”
mentioning
confidence: 99%
“…Stewardship programs are extensively used in the United States and compliance with the various recommendations is monitored annually by the National Healthcare Safety Network Annual Hospital Survey (3,4). In Spain, different scientific societies promoted the development of a consensus document for optimizing the use of antimicrobials in hospitals (PROA project) (5).…”
mentioning
confidence: 99%
“…4 In contrast, by 2015, only 48% of US hospitals nationally met all core elements of antibiotic stewardship (as defined by the Centers for Disease Control and Prevention). 39 Though we did not assess implementation of antibiotic stewardship, previous studies have shown widespread use of multiple stewardship initiatives in VA hospitals, 4 likely owing to Veterans Health Administration Directive 1031, which in 2013, established a policy for implementation and maintenance of Antimicrobial Stewardship Programs at all VA medical facilities. 4 Similar programs did not become mandatory in non-VA hospitals until 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of ID-trained leaders at small hospitals may limit antibiotic stewardship: in 2015, only 31% of hospitals with ≤50 beds met all CDC core elements. 23 Although systematic changes to attract trainees to the field of ID and to antibiotic stewardship may help, this is a long-term solution. 24,25 Other options to help distribute ID expertise across hospitals include access to expertise through quality collaboratives 26 or "tele-stewardship" in which antibiotic use data are collected remotely and ID physicians are available via a stewardship "hotline."…”
Section: Discussionmentioning
confidence: 99%